Efektivitas Penggunaan E-Modul Berorientasi Pendekatan Etnopedagogi Materi Pembelajaran Sosial Anak Usia Dini terhadap Kompetensi Pedagogik Mahasiswa - Suningsih, Taruni; Rukiyah; Andika, Windi Dwi; Ilhami, Akmillah; Anggraini, Rike; Andrianza, Yossy (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This study aims to determine the effectiveness of the use of ethnopedagogical approach-oriented e-modules in early childhood social learning materials on the pedagogical competence of prospective PAUD teacher students. The type of research used was a pre-experiment with a one group pre-test post-test design, involving 38 students as subjects. Data collection was carried out through multiple-choice objective tests in the form of pre-tests (before treatment) and post-tests (after treatment). The results of the analysis showed an average pre-test score of 63.42, and a post-test of 89.21, with an N-gain of 0.73 which is included in the high category. In addition, the percentage of class completion reached 92%. These findings indicate that the use of ethnopedagogical e-modules has proven effective in improving students' pedagogical competence. This e-module not only strengthens pedagogical understanding, but also makes social learning more meaningful and contextual, while supporting the preservation of local culture. Thus, this e-module can be an innovative digital learning media based on local wisdom, and has a positive impact on the professional readiness of students as prospective PAUD teachers.